Power and Frequency Control of Active Generator used for Smart Grid Applications - Ehsan Limouchi; Seyed Abbas Taher; Babak Ganji (Majlesi Journal of Electrical Engineering)
Nowadays, renewable energy sources such as photovoltaic and active generators are utilized frequently in modern power systems especially micro-grid. By providing electrical energy using micro-grid systems, the reliability and quality of the system can be improved. A micro-grid connected to the network depends on the main grid and consequently assessing the power quality during independent functioning (islanded mode) is important. The aim of the present work is to perform active, reactive power distribution strategies (control) for active generators used in smart grids. The proposed control method is the sliding mode which controls the active as well as reactive power and frequency. Here, based on sliding mode control method, droop control is developed for active generator. This controller is simulated for active generator by MATLAB/SIMULINK and simulation results are given. Based on the obtained simulation results, efficiency of sliding mode in regulating active and reactive power and controlling domain voltage and frequency are shown.